ORAL HEALTH IN RESIDENTS OF THE PUSKESMAS PEGIRIAN AREA: A STRUCTURAL EQUATION MODELING APPROACH - Dian Agustin Wahjuningrum; Devi Eka Juniarti; Tamara Yuanita; Setyabudi Setyabudi; Eric Priyo Prasetyo; Galih Sampoerno (LPPM Univ. Ibn Khaldun Bogor, 2026)
Oral and dental health remain major public health concerns because they significantly influence quality of life and general well-being. Although community members often demonstrate adequate knowledge and positive attitudes toward oral health, these factors do not always translate into appropriate preventive behaviors. This study aimed to analyze the structural relationship between knowledge, attitude, and oral health practices among residents in the Puskesmas Pegirian area using Structural Equation Modeling (SEM). A cross-sectional analytic study was conducted involving 250 adult participants selected through purposive sampling. Data were collected using a validated Knowledge, Attitude, and Practice (KAP) questionnaire related to oral health. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both measurement and structural models. The results demonstrated that knowledge significantly influenced attitude (β = 0.61; p < 0.001), while attitude significantly influenced oral health practice (β = 0.54; p < 0.001). Knowledge also showed a direct but weaker effect on practice (β = 0.21; p < 0.05). Attitude acted as a significant mediating variable between knowledge and oral health behavior. These findings indicate that improving knowledge alone is insufficient to promote sustainable oral health behavior without strengthening positive attitudes. Therefore, oral health promotion programs at the primary health care level should integrate behavioral reinforcement and motivational strategies to achieve long-term behavioral change.